Turning Points and Conflict Transformation in Mediation. Issue 2 (April 2014) - Jameson, Jessica Katz; Sohan, Donna; Hodge, Jenette
<x xml:space="preserve">Abstract</x> This study used a turning point framework to identify discourse that changed the nature of a mediation interaction from adversarial to cooperative. Based on Daniel Druckman's discussion of turning points, we performed a text analysis of mediation transcripts to identify disputant‐initiated and mediator‐initiated precipitants and departures in role‐played mediations. Comparing the discourse of precipitants and departures in mediations that achieved agreement only (resolution) with those that reached both agreement and evidence of relationship change (transformation) allowed us to extend previous turning point research by identifying some features of interaction in mediation that can lead to transformative outcomes. This study has implications for applying the turning point framework to mediation and practical implications for mediators.